Visual Multimedia Supported Scientific Explanation Text to Improve Elementary School Students’ Understanding of The Science Concepts - Sutinah, Cucun; Suhandi, Andi; Samsudin, Achmad (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Low understanding of concepts is one of the classic problems faced in learning science content in elementary schools. This study was conducted to test the use of visual multimedia supported scientific explanation text (VMS-SEText) in learning science content to obtain a depiction of its effectiveness in improving elementary students' conceptual understanding of the direct current circuits. Scientific Explanation text is written in computer format and the visual multimedia used in the text includes phenomenon videos, virtual animation, and dynamic analogies. The method used in this study was pre-experiment with a one-group pretest-posttest design. The research subjects were 80 students from several elementary schools in West Java Province. The data collection instrument used in this research was two types of conceptual understanding test related to the concept of direct current circuits, namely V-Type and F-Type test. The results showed that the use of VMS-SEText could facilitate around 65% of elementary school students to achieve an understanding of the concept of electrical circuits at the sound understanding level. These results indicate that the use of visual multimedia supported scientific explanation text has a moderate effectiveness in improving elementary students' conceptual understanding of direct current circuits.